2014
DOI: 10.1188/14.onf.274-285
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Patient and Treatment Factors on Adherence to Adjuvant Endocrine Therapy in Breast Cancer

Abstract: Purpose/Objectives To comprehensively assess the patient and illness or treatment factors that may predict nonadherence to adjuvant endocrine therapy and to explore whether an interaction occurs between these factors in women with breast cancer. Design Repeated-measures design. Setting The Outpatient Services of the Women's Cancer Program at the University of Pittsburgh Cancer Institute and participants' homes. Sample 91 women with early-stage breast cancer who received endocrine therapy. Methods Adher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
106
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(113 citation statements)
references
References 46 publications
(93 reference statements)
2
106
1
4
Order By: Relevance
“…For Brito et al, although many studies do not associate this variable directly, such relation may be explained by the disease severity and the presence of other comorbidities and side effects, producing different responses to treatment 6 . Presence and severity of disease symptoms are factors that might interfere in the treatment follow-up 35 . We must emphasize that although there has been significance only in the non-adjusted survival analysis, the number of specialized appointments is considered relevant.…”
Section: Discussionmentioning
confidence: 99%
“…For Brito et al, although many studies do not associate this variable directly, such relation may be explained by the disease severity and the presence of other comorbidities and side effects, producing different responses to treatment 6 . Presence and severity of disease symptoms are factors that might interfere in the treatment follow-up 35 . We must emphasize that although there has been significance only in the non-adjusted survival analysis, the number of specialized appointments is considered relevant.…”
Section: Discussionmentioning
confidence: 99%
“…Some work has evaluated relationships between HRQOL and nonadherence and nonpersistence, but results have been mixed, with some studies reporting no associations and others reporting that poor HRQOL is associated with nonadherence. 18,23,24 Findings from one recent study indicated that worse psychosocial HRQOL and greater patient distress were predictive of ET nonpersistence. 24 Evidence from previous work should be interpreted with caution, because many studies used post-ET initiation HRQOL assessments, which may be confounded by ET adverse effects, and few used BC-specific HRQOL instruments.…”
Section: Introductionmentioning
confidence: 99%
“…18,21 In addition, all studies were carried out in small cohorts of predominantly non-Hispanic white women. 14,18,23,24 The objectives of our study were to examine associations between pre-ET HRQOL and noninitiation as well as HRQOL during active treatment and nonadherence in a large, racially and socioeconomically diverse, population-based cohort of women with BC. Identifying associations between HRQOL, a modifiable factor, and inappropriate ET use offers opportunities for future interventions to reduce underuse, thus improving BC outcomes among HR-positive women.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] Limited evidence suggests early discontinuation of hormonal treatments is associated with older age 11,12 and adverse effects 13,14 and usually occurs within the first year, but may also occur in subsequent years. 15,16 However, underlying reasons for these decisions remain poorly understood. 13,17 Because AIs are oral medications that are self-administered in the home setting and started during the transitional survivorship period, 18,19 we wanted to understand what factors are associated with persistence and how these medications fit into the broader life context of older breast cancer survivors from the perspectives of the women themselves.…”
Section: Introductionmentioning
confidence: 99%